2016
DOI: 10.1177/1359105316636951
|View full text |Cite
|
Sign up to set email alerts
|

Attachment in eating-disordered outpatients with and without borderline personality disorder

Abstract: This study aims at examining the attachment states of mind in 50 female outpatients with eating disorders compared with 50 matched control participants using the Adult Attachment Interview. Moreover, the differences in attachment states of mind among eating-disordered women with and without borderline personality disorders' diagnosis were explored. The results showed an over-representation of insecure-dismissing and unresolved states of mind in clinical group compared to controls. Patients with both diagnosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 40 publications
1
16
0
5
Order By: Relevance
“…Research has shown that bodily changes following pregnancy, birth, and breastfeeding can predispose women to exacerbations of eating disorder symptoms and the development of mood symptoms during the postpartum period (Astrachan-Fletcher, Veldhuis, Lively, Fowler, & Marcks, 2008;Koubaa, Hallstrom, & Hirschberg, 2008;Micali, Simonoff, & Treasure, 2011). Prior studies also found disproportionately high incidences of unresolved attachment in women with eating disorders (Gander, Sevecke, & Buchheim, 2015;Kuipers, van Loenhout, van der Ark, & Bekker, 2016;Pace, Guiducci, & Cavanna, 2017). As an expression of a "disorder of the self" (Amianto, Northoff, Abbate Daga, Fassino, & Tasca, 2016), this result merits further examination in the postpartum period.…”
Section: Discussionmentioning
confidence: 94%
“…Research has shown that bodily changes following pregnancy, birth, and breastfeeding can predispose women to exacerbations of eating disorder symptoms and the development of mood symptoms during the postpartum period (Astrachan-Fletcher, Veldhuis, Lively, Fowler, & Marcks, 2008;Koubaa, Hallstrom, & Hirschberg, 2008;Micali, Simonoff, & Treasure, 2011). Prior studies also found disproportionately high incidences of unresolved attachment in women with eating disorders (Gander, Sevecke, & Buchheim, 2015;Kuipers, van Loenhout, van der Ark, & Bekker, 2016;Pace, Guiducci, & Cavanna, 2017). As an expression of a "disorder of the self" (Amianto, Northoff, Abbate Daga, Fassino, & Tasca, 2016), this result merits further examination in the postpartum period.…”
Section: Discussionmentioning
confidence: 94%
“…Zudem offenbaren sich beiihneneingeringerSelbstwertund eine eingeschränkte Emotionsregulationsfähigkeit (Hartmann et al 2014). Ferner berichten Studien über ein unsicheres Bindungsverhalten (Pace et al 2016). Zu dem Zusammenhang zwischen Essstörungen, deren Ausprägung und OPD-Struktur liegen bisher allerdings sehr wenige empirische Befunde vor.…”
Section: Theoretischer Hintergrundunclassified
“…On the basis of these findings, the relationship between parental adult attachment characteristics and the severity of maladaptive eating behaviors including emotional eating, and binge and purge symptoms shall be investigated within a framework of complex symptoms in both ED and SM individuals (Polivy & Herman, 2002;Pace et al, 2016;Tereno et al, 2008). Since the extent of attachment's contribution on diagnosed EDs varies across studies, this aspec t shall also be examined, especially in Eastern and Central European regions, where related data are lacking.…”
Section: Attachment Emotion Regulation and Emotional Eatingmentioning
confidence: 99%